Relationship between job satisfaction elements and organizational commitment among employees of development finance institution in Malaysia - Zaharin, Ridzuan (2014)
This study examined the relationship between the five dimensions of job satisfaction of the work itself, supervision, co-workers, promotion and salary satisfaction, with a dependent variable of organizational commitment. This study was conducted in SME Bank, one of the development finance institution (DFI) in Malaysia. Based on the data by Hewitt Associates, the turnover rate in banking and financial services in Malaysia is the second largest. High turnover among employees might jeopardize strategic plans to achieve organizational objectives. When an organization loses its critical people, there might be a number of negative impacts like reduction in overall level of innovation and quality of customer services. Therefore, organization commitment plays a very critical role in order to reduce the employees’ turnover. For this purpose, data were obtained from a sample of 150 employees in eight branches of SME Bank. The result tested on respondents/ sample to analyze the using descriptively, correlation and multiple regressions. The results showed that work satisfaction, supervision and, co-workers satisfaction were high. Meanwhile, the level of organizational commitment, promotion and salary were modest. The moderate level of organizational commitment indicated that the tendency of employees to turnover may also high. With these findings, it will become a turning point for SME Bank to identify steps that should be taken to enhance organization's commitment among its employees. This study also tested five hypotheses to determine the relationship between independent variables and dependent variable. The result shows that the dimensions of job satisfaction namely work satisfaction, supervision, co-workers, promotion and salary satisfaction have a significant relationship with organizational commitment. Overall, this study shows that job satisfaction is an important factor influencing organizational commitment. Therefore, this study suggests that the SME Bank should emphasize on job satisfaction in order to improve organizational commitment.